Seasonal workers and intra-corporate transferees in EU law: Capital’s handmaidens? - Costello, C; Freedland, M (Hart Publishing, 2016)
This chapter compares and contrasts two recent European enactments on particular forms of temporary labour migration: seasonal work and intra-corporate transfers (ICTs). Both the Seasonal Workers Directive (SWD)1 and the ICT Directive (ICTD)2 were adopted in 2014. They are typical of the EU’s piecemeal approach to labour migration, which creates a multiplicity of distinct statuses.3 We frame the comparison in light of our previous work examining the impact of migration law on labour law (section II). By way of general contribution to this collection’s themes, we also offer some observations on the challenges of regulating temporary labour migration under current conditions of globalisation (section III), and seek to explain some of the specificities of the EU’s role in regulating immigration (section IV).